Successful Pregnancy Outcome in a Patient with Protein S Deficiency: A Case Report - Khanam, Khaleda; Karim, Rehnuma; Khanum, Shakila (BIRDEM Medical Journal, 2017)
Protein S is a vitamin K-dependent anticoagulant and has a central role in the regulation of coagulation. The mechanism of action of protein S has been one of the least understood amongst the vitamin K-dependent coagulation proteins. A deficiency of protein S predisposes to recurrent thromboembolism and fetal loss. Here we report a case of protein S deficiency in a 28- year-old pregnant woman, who had a history of complete abortion at 22 of weeks of gestation and her 2nd pregnancy was managed properly with a successful fetal outcome. Birdem Med J 2016; 6(2): 134-135